Analisis hubungan antara pengeluaran pemerintah dengan ketimpangan distribusi pendapatan di Provinsi Sumatera Selatan - Ranifial Anugra; Taufiq Marwa; Imelda Imelda (Department of Development Economics, Universitas Sriwijaya, 2016)
The purpose of this study is to determine the relationship between government expenditure and inequality income distribution. This research is a quantitative research. This data is secondary data which obtained from Direktorat Jenderal Perimbangan Keuangan Kementrian Keuangan dan Sistem Informasi and Manajemen Data Dasar Regional. Granger Causality Test and Cointegration Test are used. The results of this study indicate that the form of relationship between government expenditure with income distribution inequality is one direction and not vice versa. While in the long run there is no cointegration between the variables.